Lexical features of christian tatar subdialects - (:unkn) unknown (UNIV AMAZONIA, 2018)
This article is devoted to lexical peculiarity study of baptized Tatar (Kryashens) dialects, an ethnoconfessional group of Tatars in the Volga and Ural regions living in the Republic of Tatarstan and neighboring republics and regions. Within the framework of lexical features, they analyzed the Turkic words that were outdated for the modern Tatar language, as well as the borrowings that took place in the dialects. The vocabulary of Kryashen dialects basically coincides with the common Tatar vocabulary, however there are specific features that distinguish these dialects from the Tatar literary language and its dialects. The presence of these features is conditioned by the relatively isolated development of the Kryashens from other ethnographic groups of the Tatar people. A rather large place in the dialects is occupied by words that occur in ancient Turkic language and in a number of modern Turkic and Finno-Ugric languages, for example: ariw / aru 'saint; good; clean', ardaqli - 'esteemed', kuz 'burning coal, fire', picu/pecu - 'to cut', etc. The work also examines the borrowings, most of which are Russian words, and Arab-Persian, Chuvash and Udmurt borrowings are used less. Examples are given for each group and the features of their application are determined.
Keywords: baptized Tatars; Kryashens; dialects; lexical features; ancient Turkic words; borrowings